Low-gloss UV (ultraviolet) photocureable coating as well as preparation method and application thereof

By adjusting the types and dosages of acid anhydride, hydroxyacrylate and alkylene oxide, a low viscosity monomer resin composite was prepared, which solved the problem of excessive viscosity and yellowing in UV photocured coatings, achieving low gloss, yellowing and scratch-resistant coating performance, and the solvent-free system was environmentally friendly and safe.

CN119823640APending Publication Date: 2025-04-15NANXIONG KETIAN CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510110973.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing UV light curing coatings have too high viscosity during use, are difficult to control gloss and durability, and are prone to yellowing, affecting the visual quality and service life of the product.

Method used

By adjusting the types and dosages of acid anhydride, hydroxyacrylate and alkylene oxide, a low viscosity monomer resin composite is prepared, and it is composed of low-gloss UV light curing coatings with other raw materials to avoid the use of large amounts of matting powder to maintain the performance of the coating.

Benefits of technology

It has achieved a UV light curing coating system with low gloss, yellowing resistance, scratch resistance and other properties, and the solvent-free system does not produce volatile organic compounds during the curing process, which is environmentally friendly and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005256632070000031
    Figure BDA0005256632070000031
  • Figure BDA0005256632070000061
    Figure BDA0005256632070000061
  • Figure BDA0005256632070000141
    Figure BDA0005256632070000141
Patent Text Reader

Abstract

The invention discloses a low-gloss UV photocureable coating, which is prepared from the following raw materials in parts by weight: 45 to 85 parts of monomer resin complex, 0 to 25 parts of acrylate monomer, 0 to 20 parts of aliphatic polyurethane acrylate, 1 to 10 parts of extinction powder, 0.1 to 1 part of wetting dispersant and 1 to 5 parts of photoinitiator. According to the low-gloss UV photocureable coating disclosed by the invention, the low-viscosity and adjustable-curing-speed UV photocureable coating is obtained by combining the monomer resin complex with other raw materials, a large amount of matting powder does not need to be added, and the low-gloss UV photocureable coating has low gloss, yellowing resistance and scratch resistance after being cured into a film and can be used for surface treatment of plastic products. The preparation method of the low-gloss UV photocureable coating is simple, a solvent-free system is adopted for preparation, volatile organic compounds are basically not generated in the curing and film forming process, environmental pollution is avoided, and the low-gloss UV photocureable coating is safe and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of UV light-curing materials, and in particular relates to a low-gloss UV light-curing coating and a preparation method and application thereof. Background Art

[0002] In the current coatings industry, with the enhancement of people's environmental awareness and the continuous advancement of science and technology, UV light-curing coatings are widely used in the surface treatment of various substrates such as plastics, wood, and paper due to their "5E" characteristics such as high efficiency, energy saving, economy, wide adaptability, and environmental friendliness. Especially for plastic products such as plastic floor tiles, plastic packaging, furniture finishes, and automotive interiors, UV light-curing coatings are popular because they can give plastic surfaces good anti-fouling, wear resistance and protective properties.

[0003] Monomer resin is one of the most critical and main components of UV light-curing coatings. However, in the prior art, there are still some problems in the application of traditional monomer resins such as hyperbranched acrylates and polyurethane acrylates in UV light-curing coatings. Excessively high viscosity of monomer resins will lead to difficulty in coating, unstable coating amount, and difficulty in controlling coating thickness, thus affecting the gloss and durability of the final product. In addition, UV light-curing coatings are prone to yellowing under long-term ultraviolet irradiation, which causes the coating color to become lighter and darker, thereby affecting the visual quality and service life of the product.

[0004] Since traditional UV light-curing coatings usually cannot meet the low gloss requirements of plastic parts coatings, it is often necessary to add a large amount of matting powder to solve this problem, but this sacrifices the coating adhesion, wear resistance, chemical resistance and other properties. Moreover, it is usually difficult for a single monomer resin to have low viscosity, yellowing resistance, low gloss and other properties at the same time. Therefore, it is necessary to combine monomer resins with different functional properties to construct a UV light-curing coating system with low viscosity, yellowing resistance and low gloss properties. Summary of the invention

[0005] The first object of the present invention is to provide a low-gloss UV light-curing coating to solve at least one of the above-mentioned technical problems.

[0006] The second object of the present invention is to provide a method for preparing a low-gloss UV light-curing coating to solve at least one of the above-mentioned technical problems.

[0007] The third object of the present invention is to provide an application of low-gloss UV light-curing coating to solve at least one of the above-mentioned technical problems.

[0008] According to a first aspect of the present invention, a low-gloss UV light-curing coating is provided, which comprises the following raw materials in parts by weight: 45 to 85 parts of a monomer resin complex, 0 to 25 parts of an acrylate monomer, 0 to 20 parts of an aliphatic polyurethane acrylate, 1 to 10 parts of a matting powder, 0.1 to 1 parts of a wetting dispersant and 1 to 5 parts of a photoinitiator.

[0009] According to the low-gloss UV light-curing coating of the present invention, a low-viscosity monomer resin complex is obtained by adjusting the types of raw materials. The low-gloss UV light-curing coating composed of the monomer resin complex and other raw materials does not need to add a large amount of matting powder, the curing speed is adjustable, and after curing into a film, it has the properties of low gloss, yellowing resistance, scratch resistance, etc. The monomer resin complex is used for compounding to construct a UV light-curing coating system with low gloss, yellowing resistance, scratch resistance, and good fluidity. In addition, the low-gloss UV light-curing coating of the present invention is a solvent-free system, and basically no volatile organic compounds (VOCs) are generated during the curing film forming process, avoiding environmental pollution, and being safe and environmentally friendly.

[0010] In some embodiments, the monomer resin composite is prepared by the following steps:

[0011] (1) mixing an acid anhydride, hydroxy acrylate and a polymerization inhibitor, and reacting at 100 to 130° C. until the acid value reaches 50 to 300 mgKOH / g, thereby obtaining a carboxyl compound;

[0012] (2) A carboxyl compound and a catalyst are mixed to obtain a mixture, and alkylene oxide is added to the mixture. The mixture is mixed and reacted at 85 to 130° C. until the acid value reaches 0 to 5 mgKOH / g.

[0013] In some embodiments, the monomer resin composite is prepared by the following steps:

[0014] (1) mixing an acid anhydride, hydroxy acrylate and a polymerization inhibitor, carrying out an esterification reaction at 100 to 130° C. and 300 to 400 rpm, monitoring the acid value until the acid value reaches 50 to 300 mgKOH / g, and stopping the reaction to obtain a carboxyl compound;

[0015] (2) mixing the carboxyl compound obtained in step (1) with a catalyst, mixing uniformly at 70-90° C. and 300-400 rpm to obtain a mixture, adding alkylene oxide to the mixture, carrying out a ring-opening reaction at 85-130° C. and 300-400 rpm, monitoring the acid value and stopping the reaction when the acid value is 0-5 mgKOH / g, thereby obtaining the product.

[0016] Specifically, an acid anhydride and hydroxy acrylate undergo an esterification reaction to obtain a carboxyl compound, and then the carboxyl compound undergoes a ring-opening reaction with an alkylene oxide under the catalysis of a catalyst to obtain a monomer resin complex with different functions.

[0017] In some embodiments, the amount of acid anhydride used may be 10 to 170 parts by weight, and the amount of hydroxy acrylate used may be 100 to 300 parts by weight. The acid anhydride may be selected from at least one of phthalic anhydride, maleic anhydride, succinic anhydride, dimethylmaleic anhydride, methylsuccinic anhydride, and methyltetrahydrophthalic anhydride; the hydroxy acrylate may be selected from at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, pentaerythritol triacrylate, and pentaerythritol dimethacrylate.

[0018] Therefore, when only one type of acid anhydride and hydroxy acrylate is selected, one type of acid anhydride, one type of hydroxy acrylate and propylene oxide are used as raw materials, and the resulting monomer resin composite component is relatively simple; when two or more types of acid anhydride and hydroxy acrylate are selected, multiple types of acid anhydrides, multiple types of hydroxy acrylates and propylene oxide are used as raw materials, and the resulting monomer resin composite compound is a compound.

[0019] Moreover, by adjusting the types and material ratios of acid anhydrides, hydroxy acrylates, and alkylene oxides, monomer resin composites with different functions can be obtained. For example, the monomer resin composite prepared with hydroxyethyl acrylate, maleic anhydride, and propylene oxide as raw materials has low viscosity, and its photocured film has excellent yellowing resistance and low gloss; the monomer resin composite prepared with phthalic anhydride or maleic anhydride, pentaerythritol triacrylate, and propylene oxide as raw materials has a fast curing speed, low required curing energy, and high hardness of its photocured film.

[0020] In some embodiments, the polymerization inhibitor may be selected from at least one of hydroquinone, p-hydroxyanisole, p-methoxyphenol, and tert-butylcatechol, and the amount thereof may be 0.01% to 2% of the total mass of the acid anhydride and the hydroxy acrylate.

[0021] In some embodiments, in step (2), the amount of the carboxyl compound used may be 200 to 300 parts by weight, and the amount of the alkylene oxide used may be 10 to 70 parts by weight. The alkylene oxide may be selected from at least one of propylene oxide, 1,2-butylene oxide, 1,2-tetradecane oxide, 1,2-octadecane oxide, and methylpropylene oxide.

[0022] In some embodiments, the catalyst may be selected from at least one of benzyltriethylammonium chloride, tetrabutylammonium chloride, triethylamine, and triphenylphosphine, and its usage may be 0.3% to 4% of the total mass of the carboxyl compound and the alkylene oxide.

[0023] In some embodiments, in step (1), the method for reacting at 100-130° C. until the acid value is 0-5 mgKOH / g can be as follows: first heating to 105° C., stirring and reacting for 0.5 h, then heating to 110° C., stirring and reacting for 0.5 h, and finally heating to 115° C., stirring and reacting until the acid value is 0-5 mgKOH / g.

[0024] In some embodiments, in step (2), the method of mixing and reacting at 85 to 130° C. to an acid value of 0 to 5 mgKOH / g can be to stir and react the mixture at 90° C., 95° C., 100° C., 105° C., and 110° C. for 0.5 h, and finally warming to 115° C., stirring and reacting until the acid value is 1.5 to 2.5 mgKOH / g. Specifically, gradually heating and stirring can promote the complete reaction. As the temperature increases, the movement speed of the reactant molecules accelerates and the collision frequency increases, which is conducive to effective contact and reaction between the reactant molecules. At the same time, gradually heating can also control the reaction rate more steadily, avoiding the occurrence of side reactions caused by too fast a reaction speed, thereby reducing the quality of the product.

[0025] In some embodiments, the structural formula of the monomer resin composite is as shown in formula (I):

[0026]

[0027] Wherein, R1 is an anhydride residue, R2 is one or more acrylate segments, and R3 can be C1~C 18 Specifically, R1 can be a C2-C5 straight-chain or branched alkyl group, a C2-C5 straight-chain or branched hydrocarbon group, The structural formula of R2 can be Wherein R5 can be H, a C1-C3 straight chain or branched alkyl group, and R6 can be a C1-C5 straight chain or branched alkyl group.

[0028] In some embodiments, the viscosity (25° C.) of the monomer resin composite may be 100 to 5000 cps, and the refractive index may be 1.40 to 1.47.

[0029] In some embodiments, the acrylate monomer may be selected from at least one of 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,5-pentanediol diacrylate, 1,4-decanediol diacrylate, and neopentyl glycol diacrylate.

[0030] In some embodiments, the aliphatic polyurethane acrylate can be selected from at least one of Kotian3312, Kotian3313, Kotian3214, and Kotian3211. Among them, Kotian3312 is a light yellow transparent liquid, with a viscosity (25°C) of 10000-20000 cps, a refractive index (25°C) of 1.45±0.005, a density of 1.20±0.02 g / mL, and a functionality of 2; Kotian3313 is a light yellow viscous transparent liquid, with a viscosity (25°C) of 10000-130000 cps, a refractive index (25°C) of 1.524±0.005, a density of 1.15±0.02 g / mL, and a functionality of 3. ; Kotian3214 is a slightly yellow transparent liquid with a viscosity (25°C) of 10000-25000 cps, a refractive index (25°C) of 1.483±0.005, a density of 1.10±0.02 g / mL, and a functionality of 2; Kotian3211 is a slightly yellow viscous transparent liquid with a viscosity (25°C) of 70000-90000 cps, a refractive index (25°C) of 1.494±0.005, a density of 1.27±0.02 g / mL, and a functionality of 2.

[0031] In some embodiments, the matting powder can be selected from at least one of E-1011, TS100, and AT3600. Among them, the main component of E-1011 is precipitated silica, the main component of TS100 is a silica matting powder produced by a gas phase method, and the main component of AT3600 is silica produced by a gas phase method and surface treated with polydimethylsilane.

[0032] In some embodiments, the wetting and dispersing agent may be an organosilicon wetting and dispersing agent. Specifically, the wetting and dispersing agent may be a polyether siloxane copolymer, selected from at least one of WET-267, WET-270, and HY-408. Among them, WET-267 is a water-based coating organosilicon wetting agent, the main component of which is a polyether siloxane copolymer; WET-270 is mainly composed of an alkaline urethane copolymer solution; and HY-408 is also mainly composed of a modified polyether siloxane copolymer.

[0033] In some embodiments, the photoinitiator can be selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, α,α-dimethoxy-α-phenylacetophenone, 2,4,6-trimethylbenzoylphenylethyl phosphate, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, and diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate.

[0034] According to a second aspect of the present invention, a method for preparing a low-gloss UV light-curing coating is provided, comprising the following steps: mixing a monomer resin complex, an acrylate monomer, an aliphatic polyurethane acrylate, a matting powder, a wetting dispersant and a photoinitiator to obtain a low-gloss UV light-curing coating.

[0035] The preparation method of the low-gloss UV light-curing coating of the present invention is to construct a low-gloss UV light-curing coating system with low gloss, low viscosity and high wear resistance by compounding different monomer resin composites with different functions or mixing the monomer resin composite with other monomers. The preparation method is simple and easy to control, and the preparation process does not require the use of solvents, which is green and environmentally friendly.

[0036] According to a third aspect of the present invention, there is provided an application of a low-gloss UV light-curing coating in the surface treatment of a substrate, wherein the substrate comprises a plastic product, a wood product, paper, etc., and the plastic product may be a plastic floor tile, a plastic package, a furniture facing, a car interior, or a plastic board such as a PVC board, a PP board, a PE board, or a PC board.

[0037] The low-gloss UV light-curing coating of the present invention has good overall fluidity, can be evenly covered on a substrate, especially a plastic product, when coated, has good film-forming property, and has excellent yellowing resistance and low gloss after film formation.

[0038] The beneficial effects of the present invention are:

[0039] (1) By adjusting the type and amount of acid anhydride, hydroxy acrylate and alkylene oxide, a monomer resin composite with different excellent properties can be prepared, and then the monomer resin composite is compounded to give full play to their respective performance advantages to construct a UV light-curing coating with low gloss, low viscosity, low odor, good film-forming properties, adjustable curing speed and excellent scratch resistance, which can be widely used in the field of substrates, especially plastic products.

[0040] (2) The present invention adopts an esterification reaction between an acid anhydride and a hydroxyl acrylate to prepare a carboxyl-containing acrylate, and then prepares a monomer resin composite through a ring-opening reaction with an alkylene oxide. The monomer resin composite with excellent performance is prepared through simple esterification reaction and ring-opening reaction, and then a UV light-curing coating is constructed through simple compounding. The operation process is simple and easy to control, which is conducive to large-scale and continuous production.

[0041] (3) The preparation process of the monomer resin complex and the construction strategy of the UV light-curing coating system do not use solvents. Since the present invention adopts green, environmentally friendly, efficient and energy-saving UV light-curing technology, basically no volatile organic compounds (VOCs) are generated during the film-forming process, and no large-scale pollution to the environment is caused. It meets the current high standards of society for environmental protection and is a major substitute for traditional UV light-curing coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Schematic diagram of the synthesis route of the carboxyl compound of the present invention.

[0043] Figure 2 Schematic diagram of the synthesis route of the monomer resin complex of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below in conjunction with the accompanying drawings, but the embodiments of the present invention are not limited thereto. The raw materials and reagents involved in the following examples can all be obtained from commercial channels.

[0045] The low-gloss UV light-curing coating of the present invention is mainly composed of the following raw materials in parts by weight: 45-85 parts of monomer resin complex, 0-25 parts of acrylate monomer, 0-20 parts of aliphatic polyurethane acrylate, 1-10 parts of matting powder, 0.1-1 parts of wetting dispersant and 1-5 parts of photoinitiator.

[0046] Among them, the synthetic route of the monomer resin complex of the present invention is as follows Figure 1 As shown, first, the anhydride group of the acid anhydride has a high reactivity, and the hydroxyl group of the hydroxy acrylate will attack the carbonyl carbon of the acid anhydride to open the ring structure of the acid anhydride. The hydroxy acrylate and the acid anhydride undergo an esterification reaction to obtain a carboxyl compound containing an ester bond and a carboxyl group. Then, the carboxyl hydroxyl group of the carboxyl compound undergoes a ring-opening reaction with the alkylene oxide whose epoxy ring is opened to obtain a monomer resin complex containing an ester bond and a hydroxyl group. The structural formula of the monomer resin complex can be shown as formula (I):

[0047]

[0048] Wherein, R1 is an anhydride residue, R2 is one or more acrylate segments, and R3 can be C1~C 18 Specifically, R1 can be a C2-C5 straight-chain or branched alkyl group, a C2-C5 straight-chain or branched hydrocarbon group, The structural formula of R2 can be Wherein R5 can be H, a C1-C3 straight chain or branched alkyl group, and R6 can be a C1-C5 straight chain or branched alkyl group.

[0049] It should be noted that the examples only describe several implementation methods of the method for preparing low-gloss UV light-curing coatings, and are not intended to limit the specific compounds and quantities of the raw materials of the present invention.

[0050] Matting agent can be selected from E-1011, TS100, AT3600, aliphatic polyurethane acrylate can be selected from Kotian3312, Kotian3313, Kotian3214, Kotian3211, wetting dispersant can be selected from WET-267, WET-270, HY-408. It should be noted that the above product models do not limit the raw materials of the present invention.

[0051] Example 1

[0052] This embodiment provides a method for preparing a low-gloss UV light-curing coating, comprising the following steps:

[0053] (1) Add 132 g of hydroxyethyl acrylate, 167.88 g of phthalic anhydride and 0.12 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, heat to 110° C. for 0.5 h, heat to 115° C. and continue stirring until the acid value reaches 205 to 210 mgKOH / g, and stop the reaction to obtain a carboxyl compound;

[0054] (2) Add 243 g of a carboxyl compound and 1.0 g of benzyltriethylammonium chloride to a 500 mL three-necked flask, heat to 85° C. at 350 rpm, stir evenly, then drop 56 g of propylene oxide into the three-necked flask within 2 h to obtain a mixture; then stir the mixture at 85° C., 90° C., 95° C., 100° C., 105° C., and 110° C. at 350 rpm for 0.5 h, heat to 115° C., continue stirring and reacting until the acid value reaches 1.5 to 2.5 mgKOH / g, and stop the reaction to obtain a monomer resin composite;

[0055] (3) Add 85 g of the monomer resin complex, 10 g of matting powder E-1011, 1 g of wetting dispersant WET-267 and 4 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone into a 500 mL three-necked flask and mix well to obtain a low-gloss UV light-curing coating.

[0056] Since the ring-opening reaction is the reaction of the carboxyl hydroxyl group of the monomer resin complex with the alkylene oxide, when the acid value is monitored to decrease to 1.5-2.5 mgKOH / g, the carboxyl groups in the system are basically consumed by the alkylene oxide. At this time, there is basically no carboxyl functional group in the structure, indicating the successful synthesis of the monomer resin complex.

[0057] Example 2

[0058] This embodiment provides a method for preparing a low-gloss UV light-curing coating, comprising the following steps:

[0059] (1) Add 163.41 g of hydroxyethyl acrylate, 136.44 g of maleic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, heat to 110° C. for 0.5 h, heat to 115° C., continue stirring until the acid value reaches 255 to 260 mgKOH / g, and stop the reaction to obtain a carboxyl compound;

[0060] (2) Add 233 g of a carboxyl compound and 0.9 g of benzyltriethylammonium chloride to a 500 mL three-necked flask, heat to 85° C. at 350 rpm, stir evenly, then drop 65.7 g of propylene oxide into the three-necked flask within 2 h to obtain a mixture; then stir the mixture at 85° C., 90° C., 95° C., 100° C., 105° C., and 110° C. at 350 rpm for 0.5 h, heat to 115° C., continue stirring and reacting until the acid value is 1.5 to 2.5 mgKOH / g, and stop the reaction to obtain a monomer resin composite;

[0061] (3) Add 85 g of the monomer resin complex, 10 g of matting powder E-1011, 1 g of wetting dispersant WET-267 and 4 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone into a 500 mL three-necked flask and mix well to obtain a low-gloss UV light-curing coating.

[0062] Example 3

[0063] This embodiment provides a method for preparing a low-gloss UV light-curing coating, comprising the following steps:

[0064] (1) Add 258 g of pentaerythritol triacrylate, 41.85 g of phthalic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, heat to 110° C. for 0.5 h, heat to 115° C., continue stirring and react until the acid value reaches 53 to 59 mgKOH / g, and stop the reaction to obtain a carboxyl compound;

[0065] (2) Add 282.75 g of a carboxyl compound and 0.9 g of benzyltriethylammonium chloride to a 500 mL three-necked flask, heat to 85° C. at 350 rpm, stir evenly, then drop 16.35 g of propylene oxide into the three-necked flask within 2 h to obtain a mixture; then stir the mixture at 85° C., 90° C., 95° C., 100° C., 105° C., and 110° C. at 350 rpm for 0.5 h, heat to 115° C., continue stirring and reacting until the acid value is 1.5 to 2.5 mgKOH / g, and stop the reaction to obtain a monomer resin composite;

[0066] (3) Add 85 g of the monomer resin complex, 10 g of matting powder E-1011, 1 g of wetting dispersant WET-267 and 4 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone into a 500 mL three-necked flask and mix well to obtain a low-gloss UV light-curing coating.

[0067] Example 4

[0068] This embodiment provides a method for preparing a low-gloss UV light-curing coating, comprising the following steps:

[0069] (1) Add 270.3 g of pentaerythritol triacrylate, 29.55 g of maleic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, stir and react at a speed of 350 rpm for 0.5 h, then heat to 110° C. and stir and react for 0.5 h, then heat to 115° C. and continue stirring and reacting until the acid value reaches 53 to 56 mgKOH / g, thereby stopping the reaction and obtaining a carboxyl compound;

[0070] (2) Add 280.8 g of a carboxyl compound and 0.9 g of benzyltriethylammonium chloride to a 500 mL three-necked flask, heat to 85° C. at 350 rpm, stir evenly, then drop 18.33 g of propylene oxide into the three-necked flask within 2 h to obtain a mixture; then stir the mixture at 85° C., 90° C., 95° C., 100° C., 105° C., and 110° C. at 350 rpm for 0.5 h, heat to 115° C., continue stirring and reacting until the acid value is 1.5 to 2.5 mgKOH / g, and stop the reaction to obtain a monomer resin composite;

[0071] (3) Add 85 g of the monomer resin complex, 10 g of matting powder E-1011, 1 g of wetting dispersant WET-267 and 4 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone into a 500 mL three-necked flask and mix well to obtain a low-gloss UV light-curing coating.

[0072] Example 5

[0073] This embodiment provides a method for preparing a low-gloss UV light-curing coating, comprising the following steps:

[0074] (1) Add 132 g of hydroxyethyl acrylate, 167.88 g of phthalic anhydride and 0.12 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, then heat to 110° C. for 0.5 h, then heat to 115° C. and continue stirring until the acid value reaches 205 to 210 mgKOH / g, to stop the reaction and obtain a first carboxyl compound; then take another 500 mL three-necked flask, add 243 g of the first carboxyl compound to the three-necked flask; The mixture was heated to 85°C at 350 rpm and 1.0 g of benzyltriethylammonium chloride, stirred evenly, and then 56 g of propylene oxide was added dropwise to the three-necked flask within 2 h to obtain a first mixture; the first mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C at 350 rpm for 0.5 h, and then the mixture was heated to 115°C and stirred until the acid value was 1.5-2.5 mgKOH / g, and the reaction was stopped to obtain a first monomer resin composite, which was recorded as monomer resin composite A;

[0075] (2) Add 163.41 g of hydroxyethyl acrylate, 136.44 g of maleic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, then heat to 110° C. and stir for 0.5 h, then heat to 115° C. and continue stirring until the acid value reaches 255 to 260 mgKOH / g, and stop the reaction to obtain a second carboxyl compound; then take another 500 mL three-necked flask, add 233 g of the second carboxyl compound and 0.9g benzyltriethylammonium chloride was heated to 85°C at 350rpm and stirred evenly, and then 65.7g propylene oxide was added dropwise to the three-necked flask within 2h to obtain a second mixture; then the second mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C and 110°C at 350rpm for 0.5h, and then the temperature was raised to 115°C and the stirring reaction was continued until the acid value was 1.5-2.5mgKOH / g, and the reaction was stopped to obtain a second monomer resin complex, which was recorded as monomer resin complex B;

[0076] (3) Add 258 g of pentaerythritol triacrylate, 41.85 g of phthalic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, raise the temperature to 105° C., stir and react at a speed of 350 rpm for 0.5 h, then raise the temperature to 110° C. and stir and react for 0.5 h, then raise the temperature to 115° C. and continue stirring and reacting until the acid value reaches 53 to 59 mgKOH / g, thereby stopping the reaction and obtaining a third carboxyl compound; then take another 500 mL three-necked flask, add 282.75 g of the third carboxyl compound to the three-necked flask; The mixture was heated to 85°C at 350 rpm and 0.9 g of benzyltriethylammonium chloride, stirred evenly, and then 16.35 g of propylene oxide was added dropwise to the three-necked flask within 2 h to obtain a third mixture; the third mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C and 110°C at 350 rpm for 0.5 h, and then the mixture was heated to 115°C and stirred until the acid value was 1.5-2.5 mgKOH / g, and the reaction was stopped to obtain a third monomer resin complex, which was recorded as monomer resin complex C;

[0077] (4) Add 270.3 g of pentaerythritol triacrylate, 29.55 g of maleic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, stir and react at a speed of 350 rpm for 0.5 h, then heat to 110° C. and stir and react for 0.5 h, then heat to 115° C. and continue stirring and reacting until the acid value reaches 53 to 56 mgKOH / g, thereby stopping the reaction and obtaining a fourth carboxyl compound; then take another 500 mL three-necked flask, add 280.8 g of the fourth carboxyl compound and 0.15 g of p-hydroxyanisole to the three-necked flask, and stir and react at a speed of 350 rpm for 0.5 h, then heat to 110° C. and stir and react for 0.5 h, then heat to 115° C. and continue stirring and reacting until the acid value reaches 53 to 56 mgKOH / g, thereby obtaining a fourth carboxyl compound; then take another 500 mL three-necked flask, add 280.8 g of the fourth carboxyl compound and 0.15 g of p-hydroxyanisole to the three-necked flask, and stir and react at a speed of 350 rpm for 0.5 h, then heat to 115° C. and continue stirring and reacting until the acid value reaches 53 to 56 mgKOH / g, thereby obtaining a fourth carboxyl compound; .9g benzyltriethylammonium chloride, heated to 85°C at 350rpm, stirred evenly, then 18.33g propylene oxide was added dropwise to the three-necked flask within 2h to obtain a fourth mixture; then the fourth mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C at 350rpm for 0.5h, heated to 115°C and continued to stir until the acid value was 1.5-2.5mgKOH / g, and the reaction was stopped to obtain a fourth monomer resin complex, recorded as monomer resin complex D;

[0078] (5) In a 500 mL three-necked flask, add 5.80 g of monomer resin composite A, 16.58 g of monomer resin composite B, 8.29 g of monomer resin composite C, 16.58 g of monomer resin composite D, 21.56 g of 1,6-hexanediol diacrylate, 16.58 g of aliphatic polyurethane acrylate Kotian3312, 9.12 g of matting powder E-1011, 0.5 g of wetting dispersant WET-267 and 4.99 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, mix well to obtain a low-gloss UV light-curing coating.

[0079] Example 6

[0080] This embodiment provides a method for preparing a low-gloss UV light-curing coating, comprising the following steps:

[0081] (1) Add 163.41 g of hydroxyethyl acrylate, 136.44 g of maleic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, then heat to 110° C. and stir for 0.5 h, then heat to 115° C. and continue stirring until the acid value reaches 255 to 260 mgKOH / g, and stop the reaction to obtain a second carboxyl compound; then take another 500 mL three-necked flask, add 233 g of the second carboxyl compound and 0.9g benzyltriethylammonium chloride was heated to 85°C at 350rpm and stirred evenly, and then 65.7g propylene oxide was added dropwise to the three-necked flask within 2h to obtain a second mixture; then the second mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C and 110°C at 350rpm for 0.5h, and then the temperature was raised to 115°C and the stirring reaction was continued until the acid value was 1.5-2.5mgKOH / g, and the reaction was stopped to obtain a second monomer resin complex, which was recorded as monomer resin complex B;

[0082] (2) Add 258 g of pentaerythritol triacrylate, 41.85 g of phthalic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, raise the temperature to 105° C., stir and react at a speed of 350 rpm for 0.5 h, then raise the temperature to 110° C. and stir and react for 0.5 h, then raise the temperature to 115° C. and continue stirring and reacting until the acid value reaches 53 to 59 mgKOH / g, thereby stopping the reaction and obtaining a third carboxyl compound; then take another 500 mL three-necked flask, add 282.75 g of the third carboxyl compound to the three-necked flask; The mixture was heated to 85°C at 350 rpm and 0.9 g of benzyltriethylammonium chloride, stirred evenly, and then 16.35 g of propylene oxide was added dropwise to the three-necked flask within 2 h to obtain a third mixture; the third mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C and 110°C at 350 rpm for 0.5 h, and then the mixture was heated to 115°C and stirred until the acid value was 1.5-2.5 mgKOH / g, and the reaction was stopped to obtain a third monomer resin complex, which was recorded as monomer resin complex C;

[0083] (3) Add 22.38 g of monomer resin complex B, 24.87 g of monomer resin complex C, 21.56 g of 1,6-hexanediol diacrylate, 16.58 g of aliphatic polyurethane acrylate Kotian3312, 9.12 g of matting powder E-1011, 0.5 g of wetting dispersant WET-267 and 4.99 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone into a 500 mL three-necked flask and mix well to obtain a low-gloss UV light-curing coating.

[0084] Example 7

[0085] This embodiment provides a method for preparing a low-gloss UV light-curing coating, comprising the following steps:

[0086] (1) Add 163.41 g of hydroxyethyl acrylate, 136.44 g of maleic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, then heat to 110° C. and stir for 0.5 h, then heat to 115° C. and continue stirring until the acid value reaches 255 to 260 mgKOH / g, and stop the reaction to obtain a second carboxyl compound; then take another 500 mL three-necked flask, add 233 g of the second carboxyl compound and 0.9g benzyltriethylammonium chloride was heated to 85°C at 350rpm and stirred evenly, and then 65.7g propylene oxide was added dropwise to the three-necked flask within 2h to obtain a second mixture; then the second mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C and 110°C at 350rpm for 0.5h, and then the temperature was raised to 115°C and the stirring reaction was continued until the acid value was 1.5-2.5mgKOH / g, and the reaction was stopped to obtain a second monomer resin complex, which was recorded as monomer resin complex B;

[0087] (2) Add 258 g of pentaerythritol triacrylate, 41.85 g of phthalic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, raise the temperature to 105° C., stir and react at a speed of 350 rpm for 0.5 h, then raise the temperature to 110° C. and stir and react for 0.5 h, then raise the temperature to 115° C. and continue stirring and reacting until the acid value reaches 53 to 59 mgKOH / g, thereby stopping the reaction and obtaining a third carboxyl compound; then take another 500 mL three-necked flask, add 282.75 g of the third carboxyl compound to the three-necked flask; The mixture was heated to 85°C at 350 rpm and 0.9 g of benzyltriethylammonium chloride, stirred evenly, and then 16.35 g of propylene oxide was added dropwise to the three-necked flask within 2 h to obtain a third mixture; the third mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C and 110°C at 350 rpm for 0.5 h, and then the mixture was heated to 115°C and stirred until the acid value was 1.5-2.5 mgKOH / g, and the reaction was stopped to obtain a third monomer resin complex, which was recorded as monomer resin complex C;

[0088] (3) Add 270.3 g of pentaerythritol triacrylate, 29.55 g of maleic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, stir and react at a speed of 350 rpm for 0.5 h, then heat to 110° C. and stir and react for 0.5 h, then heat to 115° C. and continue stirring and reacting until the acid value reaches 53 to 56 mgKOH / g, thereby stopping the reaction and obtaining a fourth carboxyl compound; then take another 500 mL three-necked flask, add 280.8 g of the fourth carboxyl compound and 0.15 g of p-hydroxyanisole to the three-necked flask, and stir and react at a speed of 350 rpm for 0.5 h, then heat to 110° C. and stir and react for 0.5 h, then heat to 115° C. and continue stirring and reacting until the acid value reaches 53 to 56 mgKOH / g, thereby obtaining a fourth carboxyl compound; then take another 500 mL three-necked flask, add 280.8 g of the fourth carboxyl compound and 0.15 g of p-hydroxyanisole to the three-necked flask, and stir and react at a speed of 350 rpm for 0.5 h, then heat to 115° C. and continue stirring and reacting until the acid value reaches 53 to 56 mgKOH / g, thereby obtaining a fourth carboxyl compound; .9g benzyltriethylammonium chloride, heated to 85°C at 350rpm, stirred evenly, then 18.33g propylene oxide was added dropwise to the three-necked flask within 2h to obtain a fourth mixture; then the fourth mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C at 350rpm for 0.5h, heated to 115°C and continued to stir until the acid value was 1.5-2.5mgKOH / g, and the reaction was stopped to obtain a fourth monomer resin complex, recorded as monomer resin complex D;

[0089] (4) Add 22.38 g of monomer resin complex B, 8.29 g of monomer resin complex C, 16.58 g of monomer resin complex D, 21.56 g of 1,6-hexanediol diacrylate, 16.58 g of aliphatic polyurethane acrylate Kotian3312, 9.12 g of matting powder E-1011, 0.5 g of wetting dispersant WET-267 and 4.99 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone into a 500 mL three-necked flask and mix well to obtain a low-gloss UV light-curing coating.

[0090] Example 8

[0091] This embodiment provides a method for preparing a low-gloss UV light-curing coating, comprising the following steps:

[0092] (1) Add 132 g of hydroxyethyl acrylate, 167.88 g of phthalic anhydride and 0.12 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, then heat to 110° C. for 0.5 h, then heat to 115° C. and continue stirring until the acid value reaches 205 to 210 mgKOH / g, to stop the reaction and obtain a first carboxyl compound; then take another 500 mL three-necked flask, add 243 g of the first carboxyl compound to the three-necked flask; The mixture was heated to 85°C at 350 rpm and 1.0 g of benzyltriethylammonium chloride, stirred evenly, and then 56 g of propylene oxide was added dropwise to the three-necked flask within 2 h to obtain a first mixture; the first mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C at 350 rpm for 0.5 h, and then the mixture was heated to 115°C and stirred until the acid value was 1.5-2.5 mgKOH / g, and the reaction was stopped to obtain a first monomer resin composite, which was recorded as monomer resin composite A;

[0093] (2) Add 163.41 g of hydroxyethyl acrylate, 136.44 g of maleic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, heat to 105° C., stir at 350 rpm for 0.5 h, then heat to 110° C. and stir for 0.5 h, then heat to 115° C. and continue stirring until the acid value reaches 255 to 260 mgKOH / g, and stop the reaction to obtain a second carboxyl compound; then take another 500 mL three-necked flask, add 233 g of the second carboxyl compound and 0.9g benzyltriethylammonium chloride was heated to 85°C at 350rpm and stirred evenly, and then 65.7g propylene oxide was added dropwise to the three-necked flask within 2h to obtain a second mixture; then the second mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C and 110°C at 350rpm for 0.5h, and then the temperature was raised to 115°C and the stirring reaction was continued until the acid value was 1.5-2.5mgKOH / g, and the reaction was stopped to obtain a second monomer resin complex, which was recorded as monomer resin complex B;

[0094] (3) Add 258 g of pentaerythritol triacrylate, 41.85 g of phthalic anhydride and 0.15 g of p-hydroxyanisole to a 500 mL three-necked flask, raise the temperature to 105° C., stir and react at a speed of 350 rpm for 0.5 h, then raise the temperature to 110° C. and stir and react for 0.5 h, then raise the temperature to 115° C. and continue stirring and reacting until the acid value reaches 53 to 59 mgKOH / g, thereby stopping the reaction and obtaining a third carboxyl compound; then take another 500 mL three-necked flask, add 282.75 g of the third carboxyl compound to the three-necked flask; The mixture was heated to 85°C at 350 rpm and 0.9 g of benzyltriethylammonium chloride, stirred evenly, and then 16.35 g of propylene oxide was added dropwise to the three-necked flask within 2 h to obtain a third mixture; the third mixture was stirred at 85°C, 90°C, 95°C, 100°C, 105°C and 110°C at 350 rpm for 0.5 h, and then the mixture was heated to 115°C and stirred until the acid value was 1.5-2.5 mgKOH / g, and the reaction was stopped to obtain a third monomer resin complex, which was recorded as monomer resin complex C;

[0095] (4) Add 5.80 g of monomer resin complex A, 16.58 g of monomer resin complex B, 24.87 g of monomer resin complex C, 21.56 g of 1,6-hexanediol diacrylate, 16.58 g of aliphatic polyurethane acrylate Kotian3312, 9.12 g of matting powder E-1011, 0.5 g of wetting dispersant WET-267 and 4.99 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone into a 500 mL three-necked flask and mix well to obtain a low-gloss UV light-curing coating.

[0096] Comparative Example 1

[0097] This comparative example provides a method for preparing a UV light-curing coating, comprising the following steps:

[0098] To a 500 mL three-necked flask, 85 g of hyperbranched resin Kotian 7810, 10 g of matting powder E-1011, 1 g of wetting and dispersing agent WET-267 and 4 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone were added and mixed evenly to obtain a UV light-curing coating.

[0099] The raw material Kotian7810 used is an acrylate oligomer, which is a commercially available product owned by the applicant.

[0100] Comparative Example 2

[0101] This comparative example provides a method for preparing a UV light-curing coating, comprising the following steps:

[0102] To a 500 mL three-necked flask, add 85 g of epoxy acrylate Kotian 4212, 10 g of matting powder E-1011, 1 g of wetting and dispersing agent WET-267 and 4 g of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, mix well, and obtain a UV light-curing coating.

[0103] The raw material Kotian 4212 used is a difunctional epoxy acrylate containing TPGDA, which is a commercially available product owned by the applicant.

[0104] Comparative Example 3

[0105] This comparative example provides a method for preparing a UV light-curing coating, comprising the following steps:

[0106] To a 500-mL three-necked flask, add 5.80 g Kotian 5310, 16.58 g tripropylene glycol diacrylate, 8.29 g nine-functional aliphatic polyurethane Kotian 3910, 16.58 g hyperbranched resin Kotian 7810, 21.56 g 1,6-hexanediol diacrylate, 16.58 g aliphatic polyurethane acrylate Kotian 3312, 9.12 g matting powder E-1011, 0.5 g wetting dispersant WET-267 and 4.99 g photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, mix well to obtain a UV light-curing coating.

[0107] Among them, the raw material Kotian5310 used is a polyether-type aromatic difunctional polyurethane, and Kotian5310, Kotian3910 and Kotian3312 are all commercially available products owned by the applicant.

[0108] Test Example 1

[0109] In this test example, the monomer resin composites prepared in Examples 1 to 4, the hyperbranched resin Kotian 7810 of Comparative Example 1, and the epoxy acrylate Kotian 4212 of Comparative Example 2 were tested for chromaticity, viscosity, acid value, and refractive index.

[0110] The test methods for each test are as follows:

[0111] (1) Chroma test: Test according to the method of national standard GB / T 1722-1992;

[0112] (2) Viscosity test: Tested according to the method of national standard GB / T 2794-2022;

[0113] (3) Acid value test: Test according to the method of national standard GB / T 5530-2005;

[0114] (4) Refractive index test: Test according to the method of national standard GB / T 6488-2022.

[0115] Table 1 Comprehensive test results of monomer resin composite

[0116]

[0117]

[0118] The test results are shown in Table 1. From the chromaticity test results, the chromaticity of the monomer resin complex prepared in Examples 1 to 4 is comparable to that of commercial hyperbranched resins. From the viscosity test results, the viscosity of the monomer resin complex prepared in Examples 1 to 4 is measured to be 150-4000, which is comparable to the viscosity of the hyperbranched resin Kotian7810, but much lower than the viscosity of the hyperbranched resin Kotian4212, indicating that the monomer resin complex prepared in Examples 1 to 4 can be used as a resin raw material to prepare coatings. Among them, the viscosity of the monomer resin complex of Example 2 is much lower than that of the comparative example, because the molecular weight of the raw material used in Example 2 is small, and the structure of the monomer resin complex is simple, without a complex branched structure, and the interaction force between molecules is weak. From the refractive index test results, the refractive index of the monomer resin complex prepared in Examples 1 to 4 is lower than that of commercial hyperbranched resins, and the light transmittance is good. After observation, the monomer resin complex prepared in Examples 1 to 4 and the resins in Comparative Examples 1 and 2 all have a clear and transparent appearance. From the test results, the monomer resin composite exhibits clear and transparent appearance, low viscosity and good light transmittance. In addition, the low viscosity and the residual hydroxyl polar functional groups in the preparation process of the monomer resin composite can improve the pigment wettability.

[0119] Test Example 2

[0120] In this test example, after the low-gloss UV light-curing coatings prepared in Examples 1 to 4 and the UV light-curing coatings prepared in Comparative Examples 1 to 2 were cured into films, hardness, yellowing resistance, glossiness and abrasion resistance tests were performed to verify the comprehensive performance of the low-gloss UV light-curing coatings of Examples 1 to 4.

[0121] The preparation method of the cured film is to use a paint film scraper to apply the UV light-curing coating on black and white paper respectively, with a coating thickness of 25 μm, and then irradiate the black and white paper under the light source of a UV light curing machine for curing, use the finger contact method to judge the surface dryness, and record the curing energy.

[0122] The test methods for each test are as follows:

[0123] (1) Hardness test: Test according to the method of national standard GB / T 6739-1996.

[0124] (2) Yellowing resistance test: The test is carried out in accordance with the method of national standard GB / T 23983-2009.

[0125] (3) Gloss test: Test according to the method of national standard GB / T 9754-2007.

[0126] Table 2 Comprehensive performance test results of UV light-cured films of Examples 1 to 4 and Comparative Examples 1 to 2

[0127]

[0128] Table 2 shows the comprehensive performance test results of UV light-cured films. It can be seen from Table 2 that the low-gloss UV light-cured coatings of Examples 3 and 4 require the lowest curing energy, which is 100 mJ / cm 2From the perspective of curing energy, the curing energy of the UV light-cured film of Comparative Example 1 is 1.5 times that of Example 3, and the curing energy of the UV light-cured film of Comparative Example 2 is 2 times that of Example 3, indicating that the curing speed of the low-gloss UV light-cured coatings of Examples 3 and 4 is faster than that of other resins. From the gloss test results, it can be seen that the gloss of the cured film obtained by curing the low-gloss UV light-cured coating of Example 2 is as low as 2.5 (white segment) and 0.4 (black segment), which is significantly lower than the gloss of Comparative Examples 1 and 2. The reason is that the viscosity of the monomer resin composite of Example 2 is low, and on the other hand, compared with other examples and comparative examples, the monomer resin composite of Example 2 has fewer active functional groups, a low degree of crosslinking, and the raw materials do not contain a benzene ring structure. The glossiness of the UV light-cured films prepared in Example 1, Example 3 and Example 4 is comparable to that of the UV light-cured film prepared in Comparative Example 1, and is approximately 70% of that of the UV light-cured film prepared in Comparative Example 2. It can be seen that the glossiness of the low-gloss UV light-cured coating of the present invention after curing is comparable to that of the cured film prepared by the hyperbranched resin, and the glossiness of some UV light-cured films is even significantly reduced, indicating that the monomer resin composite of the present invention has application potential in low-gloss UV light-cured coatings. From the hardness test results, it can be seen that the hardness of the UV light-cured films prepared in Example 3 and Example 4 reached 2H and 3H, respectively, and their hardness is comparable to that of the UV light-cured film prepared in Comparative Example 1 using commercial hyperbranched resin and the UV light-cured film prepared in Comparative Example 2 using commercial epoxy acrylate, indicating that they have good resistance to local deformation and have the potential to be used as scratch-resistant materials. From the yellowing resistance test results, it can be seen that the yellowing resistance of the UV light-cured films prepared in Example 1 and Example 2 is the best among all the examples and comparative examples, indicating that Example 1 and Example 2 successfully constructed a UV light-cured coating system with yellowing resistance. The above test results show that Examples 1 to 4 of the present invention can obtain different monomer resin composites by selecting the types of anhydride and hydroxy acrylate, which can be used to prepare UV light-curing coatings with excellent properties such as low gloss, high hardness, and yellowing resistance.

[0129] Test Example 3

[0130] This test example conducts comprehensive tests on the UV light-curing coatings of Examples 5 to 8 and Comparative Example 3 to verify the comprehensive performance of the low-gloss UV light-curing coatings of Examples 5 to 8.

[0131] The test methods for each test in the comprehensive test are as follows:

[0132] (1) Abrasion resistance test: The abrasion resistance of the UV light-cured film was tested using a thimble. A thimble with a diameter of 0.02 mm was used to scratch the UV light-cured film for 200 mm under a weight of 150 g, and the length without scratches was recorded.

[0133] (2) Adhesion test: The test was conducted according to the 100-grid test method of ASTM D3359.

[0134] (3) Touch test: Feel the coating surface by hand to feel the coating hardness, smoothness, etc.

[0135] (4) Gloss test: Test according to the method of national standard GB / T 9754-2007.

[0136] (5) Paint fluidity test: Observe the fluidity of UV light-curing paint by visual inspection.

[0137] Table 3 Comprehensive performance test results of UV light curing coatings of Examples 5 to 8 and Comparative Example 3

[0138]

[0139] Table 3 shows the comprehensive performance test results of the UV light-curing coatings of Examples 5 to 8 and Comparative Example 3. As can be seen from Table 3, in the abrasion resistance test, when a pin is used to scratch the same length on the surface of the UV light-curing film, the length of no scratch on the UV light-curing film of Examples 5 to 8 is between 135 and 153 mm, while the length of no scratch on the UV light-curing film of Comparative Example 3 is only 2 mm, indicating that the UV light-curing films of Examples 5 to 8 have better scratch resistance. The UV light-curing films of Examples 5 to 8 have the same adhesion level as the UV light-curing film of Comparative Example 3, but due to the presence of the monomer resin composite B, the glossiness (black segment is between 1.0° and 1.6°, white segment is between 3.3° and 4.9°) and yellowing resistance value (between 5.74 and 5.96) of the former are lower than those of the latter (black segment 5.0°, white segment 9.3°, yellowing resistance value 6.59), and the UV light-curing films obtained by curing of Examples 5 to 8 have a better feel when the surface hardness and smoothness of the UV light-curing films are felt by touch. By observing the UV light-curing coatings prepared in Examples 5 to 8 and Comparative Example 3, it was found that the low-gloss UV light-curing coatings of Examples 5 to 8 were fluid, while the UV light-curing coating of Comparative Example 3 was jelly-like and had no fluidity, indicating that the low-gloss UV light-curing coatings of Examples 5 to 8 were easier to apply to the substrate material than the UV light-curing coatings of the Comparative Example.

[0140] In summary, Examples 5 to 8 successfully construct a low-gloss UV light-curing coating that combines the performance advantages of different monomer resin composites through the compounding of the monomer resin composites prepared in Examples 1 to 4. The low-gloss UV light-curing coating has good overall fluidity and adjustable curing speed, which is more conducive to coating. The performance of the UV light-curing film also brings out the performance advantages of the various UV light-curing films prepared in Examples 1 to 4. It not only has good surface hardness and smoothness, but also exhibits yellowing resistance, scratch resistance, low gloss and other characteristics. It can be used as a low-gloss UV light-curing coating for plastic products.

[0141] Of course, in other embodiments, monomer resin composites with different functions may be compounded to meet actual use requirements.

[0142] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. Low gloss UV light curing coating, characterized in that: The invention comprises the following raw materials in parts by weight: 45 to 85 parts of monomer resin complex, 0 to 25 parts of acrylate monomer, 0 to 20 parts of aliphatic polyurethane acrylate, 1 to 10 parts of matting powder, 0.1 to 1 part of wetting dispersant and 1 to 5 parts of photoinitiator.

2. The low gloss UV light curing coating according to claim 1, characterized in that: The monomer resin composite is prepared by the following steps: (1) mixing an acid anhydride, hydroxy acrylate and a polymerization inhibitor, and reacting at 100 to 130° C. until the acid value reaches 50 to 300 mgKOH / g, thereby obtaining a carboxyl compound; (2) The carboxyl compound and the catalyst are mixed to obtain a mixture, and alkylene oxide is added to the mixture. The mixture is mixed and reacted at 85 to 130° C. until the acid value reaches 0 to 5 mgKOH / g.

3. The low gloss UV light curing coating according to claim 2, characterized in that: In parts by weight, the acid anhydride is used in an amount of 10 to 170 parts, and the hydroxy acrylate is used in an amount of 100 to 300 parts.

4. The low gloss UV curing coating according to claim 2 or 3, characterized in that: The acid anhydride is selected from at least one of phthalic anhydride, maleic anhydride, succinic anhydride, dimethylmaleic anhydride, methylsuccinic anhydride, and methyltetrahydrophthalic anhydride; the hydroxy acrylate is selected from at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, pentaerythritol triacrylate, and pentaerythritol dimethacrylate.

5. The low gloss UV light curing coating according to claim 4, characterized in that: The polymerization inhibitor is selected from at least one of hydroquinone, p-hydroxyanisole, p-methoxyphenol and tert-butylcatechol, and its usage is 0.01% to 2% of the total mass of the acid anhydride and the hydroxy acrylate.

6. The low gloss UV light curing coating according to claim 2, characterized in that: In parts by weight, the amount of the carboxyl compound is 200 to 300 parts, the amount of the alkylene oxide is 10 to 70 parts; the alkylene oxide is selected from at least one of propylene oxide, 1,2-butylene oxide, 1,2-tetradecane oxide, 1,2-octadecane oxide and methylpropylene oxide.

7. The low gloss UV light curing coating according to claim 2 or 6, characterized in that: The catalyst is selected from at least one of benzyltriethylammonium chloride, tetrabutylammonium chloride, triethylamine and triphenylphosphine, and its usage is 0.3% to 4% of the total mass of the carboxyl compound and the alkylene oxide.

8. The low gloss UV light curing coating according to claim 1, characterized in that: The acrylate monomer is at least one selected from 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,5-pentanediol diacrylate, 1,4-decanediol diacrylate, and neopentyl glycol diacrylate.

9. The method for preparing the low-gloss UV light-curing coating according to claim 1, characterized in that: The following steps are involved: The monomer resin complex, acrylate monomer, aliphatic polyurethane acrylate, matting powder, wetting dispersant and photoinitiator are mixed to obtain the product.

10. Use of the low-gloss UV light-curing coating according to claim 1 in substrate surface treatment.